Research of Joining Brittle Nonmetallic Materials with an Active Solder - Roman Koleňák; Michal Prach (Advances in Materials Science and Engineering)
This paper deals with soldering high-purity brittle, nonmetallic materials such as SiO2, Si, and C (graphite). However, these materials exert poor wettability when using tin solder. Therefore, to reduce the wetting angle, an Sn solder alloyed with active Ti element was used. At a soldering temperature of 860°C and 15 min soldering time, the wetting angle on SiO2 ceramics was 30°, on silicon 42°, and on graphite 52°. All these wetting angles are below 90° and are acceptable for soldering. It has been shown that the bond in all joined materials (SiO2, Si, and C) was of a diffusion character. New intermetallic products were formed on the boundary with nonmetal, thus allowing bond formation. The shear strength of SiO2 ceramics attained an average value of 17 MPa.